MRI in sarcoglycanopathies: a large international cohort study. Issue 1 (9th September 2017) - Tasca, Giorgio; Monforte, Mauro; Díaz-Manera, Jordi; Brisca, Giacomo; Semplicini, Claudio; D'Amico, Adele; Fattori, Fabiana; Pichiecchio, Anna; Berardinelli, Angela; Maggi, Lorenzo; Maccagnano, Elio; Løkken, Nicoline; et al.
Abstract : Objectives: To characterise the pattern and spectrum of involvement on muscle MRI in a large cohort of patients with sarcoglycanopathies, which are limb-girdle muscular dystrophies (LGMD2C–2F) caused by mutations in one of the four genes coding for muscle sarcoglycans. Methods: Lower limb MRI scans of patients with LGMD2C–2F, ranging from severe childhood variants to milder adult-onset forms, were collected in 17 neuromuscular referral centres in Europe and USA. Muscle involvement was evaluated semiquantitatively on T1-weighted images according to a visual score, and the global pattern was assessed as well. Results: Scans from 69 patients were examined (38 LGMD2D, 18 LGMD2C, 12 LGMD2E and 1 LGMD2F). A common pattern of involvement was found in all the analysed scans irrespective of the mutated gene. The most and earliest affected muscles were the thigh adductors, glutei and posterior thigh groups, while lower leg muscles were relatively spared even in advanced disease. A proximodistal gradient of involvement of vasti muscles was a consistent finding in these patients, including the most severe ones. Conclusions: Muscle involvement on MRI is consistent in patients with LGMD2C–F and can be helpful in distinguishing sarcoglycanopathies from other LGMDs or dystrophinopathies, which represent the most common differential diagnoses. Our data provide evidence about selective susceptibility or resistance to degeneration of specific muscles when one of the sarcoglycans is deficient, as well as preliminary information about progressive involvement of the different muscles over time.